CARBAPENEM RESISTANT ACINETOBACTER-A MAJOR PATHOGEN IN A TERTIARY CARE HOSPITAL: Carbapenem Resistant Acinetobacter - Babar, Nazish; Usman, Javaid; Munir, Tehmina; Gill, Maria Mushtaq; Latif, Mahwish; Gilani, Mehreen; Anjum, Rabia (Pakistan Armed Forces Medical Journal, 2015)
Objective: To determine the frequency of carbapenem resistant Acinetobacter in the Military Hospital Rawalpindi, Pakistan. Study Design: Descriptive study. Place and Duration of Study: Department of Microbiology, Army Medical College, from Oct, 2012 to Feb, 2013. Material and Methods: Clinical specimens like naso-bronchial lavage, blood, pus, sputum and catheter tips were inoculated on blood agar and Mac Conkey agar while the urine samples were inoculated on Cystine Lactose Electrolyte Deficient (CLED) agar. Acinetobacter spp. isolated, were later subjected to antimicrobial susceptibility testing using the modified Kirby-Bauer disc diffusion method on Mueller Hinton agar as per Clinical Laboratory and Standards Institute (CLSI) guidelines. Results: Out of a total of 85 Acinetobacter spp. 62 isolates were found to be carbapenem resistant. They were also found to be 100% resistant to ciprofloxacin and ceftriaxone thus becoming multidrug resistant followed by tazobactam piperacillin (98%) and trimethoprim sulphamethoxazole (92%). Minimum resistance was seen against tigecycline being 21%. Conclusion: It is concluded from our study that there is a high frequency (72.94%) of resistance to carbapenems in Acinetobacter spp. in our setup which is associated with increased morbidity and mortality due to limited treatment options.